Tree regeneration and spatial patterning among midtolerant tree species following gap-based harvesting in a temperate hardwood forest - Schnake, David K.; Forrester, Jodi A.; Sánchez Meador, Andrew J.; Mladenoff, David J.; Lorimer, Craig G. (Frontiers in Forests and Global Change, 2023)
Abstract Field experiments of gap-based harvest systems in temperate northern hardwood forests have provided inconsistent support for the theory that such regeneration approaches can improve regeneration success among increasingly underrepresented tree species intermediate in shade tolerance. We established a field experiment in Wisconsin, USA testing the long-term response of tree regeneration to group selection harvesting that created small (50 m2 - D:H 0.32), medium (200 m2 – D:H 0.64) and large (380 m2 – D:H 0.88) gaps. Light levels were modeled to test the assumption of resource heterogeneity within and across these gap sizes. Spatial statistics were used to assess whether the point patterns of saplings of several midtolerant tree species (Betula alleghaniensis, Carya cordiformis, Fraxinus spp.) mapped in harvest gaps provided evidence for partitioning across resource gradients nine years post-harvest. Finally, we measured occurrence and height of all saplings within the harvest gaps to test the effects of gap size and deer exclusion fencing on the density and total height of shade-tolerant and midtolerant tree regeneration. Light levels progressively increased with gap size, varied by position within gaps, and provided significant evidence of resource heterogeneity. The complex light gradients formed both within and across the three gap sizes may partially explain the statistically significant clustering of Fraxinus spp. saplings in gap centers and north and east into the forested edge of medium and large gaps, C. cordiformis on the west sides of forested transitions surrounding large gaps, and B. alleghaniensis in the centers of large gaps. Densities of tolerant and midtolerant saplings were similar in medium and large gaps after nine growing seasons, though tolerant saplings averaged two meters taller across all three gap sizes. Our results show that gap-based silvicultural systems can create resource gradients that are sufficient to regenerate mixtures of species with high to intermediate tolerance of shade. However, prescriptions beyond harvesting and deer exclusion fencing may be necessary for the recruitment of midtolerant species to canopy positions.